Palaeozoic arthropods in Baltoscandian erratics from the coastal cliffs near Gdynia in northern Poland - Kowalewska, Agata; Jagt-Yazykova, Elena (Geologos, 2025)
Fossils recovered from Baltoscandian erratic boulders and cobbles, collected on the beach near Orłowo and Oksywie Cliff (the latter for the first time) near Gdynia in northern Poland constitute an interesting lot. Several trilobite taxa have been discovered, such as Calymene? sp., Acaste? sp., Chasmopsinae indet., Encrinurus sp. and Proetidae indet. Another group of arthropods represented here is Ostracoda, mostly comprising taxa of the family Beyrichiidae, assigned to the order Palaeocopida. The preservation of all fossils certainly leaves much to be desired. Nevertheless, after preparation it has turned out possible to provide some taxonomic identification and the estimated stratigraphical provenance of the erratics studied. In addition, on the basis of taxonomic composition, palaeoecological and palaeogeographical patterns have been worked out. The present paper ranks amongst the very few recent publications dedicated to erratic fossils from Poland in general and those on arthropods specifically.